Analyzing cross‐talk of EPO and EGF genes along with evaluating therapeutic potential of Cinnamomum verum in cigarette‐smoke‐induced lung pathophysiology in rat model. Issue 3 (11th January 2023) - Anwar, Haseeb; Navaid, Soha; Muzaffar, Humaira; Hussain, Ghulam; Faisal, Muhammad Naeem; Ijaz, Muhammad Umar; Riđanović, Sanel
Abstract: The integrity of the distal alveolar epithelium is crucial for lung regeneration following an injury. The present study aimed to evaluate the effect of Cinnamomum verum extract; cross‐talk of epidermal growth factor ( EGF ) and erythropoietin ( EPO ) genes in a smoke‐induced lung injury rat model. For experimentation ( n = 27), albino rats were divided equally into three groups, i.e., negative control (NC), positive control (PC), and treatment group (TG). Cigarette smoke was exposed to PC and TG (4 CG/day). C. verum was given orally (350 mg/kg body weight) for 21 days. Decapitation ( n = 3) was done on 14th, 18th, and 21st days, respectively. Analyses (hematology, biochemical, high performance liquid chromatography [HPLC], histology, and gene expression) were carried out and results were statistically analyzed by two‐way analysis of variance. HPLC analysis of ethanolic extract of C. verum was done to identify the presence of phenolic constituents which showed high concentrations of quercetin and P‐coumaric acid. Serum oxidative parameters such as total oxidant status, malondialdehyde, and hematological parameters such as red blood cells, hemoglobin, hematocrit, and white blood cells were significantly ( p < .05) elevated in the PC group; however, these parameters were significantly ( p < .05) improved in TG. While total antioxidant capacity and serum parameters such as total protein, albumin, and globulin were significantly ( p < .05) reduced in the PC group but significantly improved ( p < .05) in TG. Histological analysis revealed that smoke exposure resulted in a measurable increase in alveolar septal thickening while ethanolic extract of C. verum greatly ameliorated the histopathological changes in the lung alveoli. The gene expression analysis of EGF and EPO genes showed a significant upregulation ( p < .05) of both genes in PC group while in TG, the level of both genes downregulated, in which lung damage was ameliorated due to cytoprotective effects of ethanolic extract of C. verum. Abstract : Histological analysis revealed that smoke exposure resulted in a measurable increase in alveolar septal thickening while ethanolic extract of Cinnamomum verum greatly ameliorated the histopathological changes in the lung alveoli.